Corporate governance, research and development volatility and firm performance: Evidence from Spain and Ireland - Geeta Duppati; Albert Sune; Navajyoti Samanta (Cogent Economics & Finance, 2017)
The present study sheds light on the comparative experiences of the two countries originating from differing legal systems and describes how their codes and practices affect the publicly listed firms' performance. It investigates the linkages between Research and Development (R&D) expenditures, Board characteristics and firm performance using a sample of Irish and Spanish firms for the period 2005-2014. To do this, the study uses ROA and Tobin's Q as proxies for financial performance; and board size, non-executive directors, female representation and CEO duality as board structure characteristics; and R&D expenditure volatility, employing different techniques that include OLS, fixed effects model and Quantile regression model. The difference-in-difference model is used to verify the significance of robustness of relationships considering the global financial crisis as an exogenous shock. The descriptive statistics suggests a comparability of boards' independence for the Spanish- and Irish-listed firms. Although the Spanish firms are less dual than Irish firms, the results are comparable on the association between CEO duality and firm performance. The findings of Spanish-listed firms on the relationship between increase and decrease in the R&D expenditures volatility and performance support the creative-destructive perspective that suggests effective governance in funding allocation to R&D.
Keywords: G30; G32; G34; N24; 330; research and development volatility; boards; corporate governance; creative-destructive perspective; Spanish- and Irish-listed firms; difference-in-difference model